The Influence of Internet Banking on the Efficiency and Cost Savings for Banks’ Customers - Jolly, Vidhya (International Journal of Social Sciences and Management, 2016)
The world is developing; the internet has become one important tool in life. Its proper use can create wonders. This research paper is about how the internet is used by Indian banks and how it has changed the face of banking. The study is limited to Kochi alone. Internet banking has its advantages: primarily it is cost efficient. Using internet banking customers can do most of their bank transactions online; almost all of the transactions are possible. Adding to the advantages these transactions require only an internet connection and a computer. These facilities are not limited to the working hours of the bank; one can avail these services24 hours a day, 7 days a week. But proficiency to use these facilities properly is the main challenge. This study is based upon the review taken from part of the Kochi population who are Customers of State Bank of India and ICICI bank. Day by day customers using internet banking is on the rise. Also, internet banking is not limited to the bank transactions alone, it can be used as a mode of payment to registered merchants. This makes the regular payments, like that of electricity, water, mobile bill etc. very easy. Any tool can be efficient only if it is used properly. How cost effective and popular is the usage of online banking tool in Kochi is the major problem under investigation. Int. J. Soc. Sc. Manage. Vol. 3, Issue-3: 163-170